Two new species of the genus Camponotus Mayr, 1861 (Hymenoptera: Formicidae) with five new records from India - Dhadwal, Tarun; Bharti, Himender (European Journal of Taxonomy, 2023)
Two new species, Camponotus sholensis sp. nov. and Camponotus meghalayaensis sp. nov. are described from India and redescriptions of four species (C. habereri Forel, 1911, C. keihitoi Forel, 1913, C. quadrinotatus Forel, 1886 and C. simoni Emery, 1893) new to India are provided. We also recorded and described an unidentified form ‘Camponotus sp. 101’ that does not correspond to any species already known in India. An identification key supplemented with digital images of the known species of the genus is also provided.